Meta-Analysis of the Effect of Realistic Mathematics Education Supported by Mathematical Software on Students’s Mathematical Ability - Maximus Tamur; Eliterius Sennen; Feliciana Maria Vaz (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Mathematics education continues to seek practical instructional approaches that enhance students' conceptual understanding and foster problem-solving abilities through creative and critical thinking, aligned with Bloom's Taxonomy of Educational Objectives. This study contributes novel insights by integrating Realistic Mathematics Education (RME) supported by mathematics software within a meta-analytic framework, thereby providing a comprehensive examination of their combined effects and magnitude. The purpose of this meta-analysis was to investigate the overall impact of RME supported by mathematics software on students' mathematical abilities across multiple empirical studies. The analysis was conducted using peer-reviewed articles published in reputable international journals, with inclusion criteria based on research design, sample characteristics, and intervention features. A total of 14 studies met the eligibility criteria and were included in the analysis. Statistical procedures were employed to calculate effect sizes, assess heterogeneity, examine potential moderating variables, and determine them. Although the study was limited by the availability of high-quality empirical research and the potential for publication bias, the results provide robust evidence that integrating RME and mathematics software significantly increases students' mathematical abilities. These findings underscore the importance of technology-enhanced pedagogical strategies and offer valuable implications for educators, researchers, and policymakers seeking to advance the quality of mathematics education